THE SCHOOL PRINCIPAL’S LEADERSHIP STRATEGY IN ENHANCING THE PERFORMANCE OF SCHOOL OPERATORS IN MANAGING DAPODIK: A CASE STUDY AT SMAN 1 MUARA BATU - Marlina, Marlina; Marsithah, Iis; Khairani, Cut (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to investigate strategic planning, explore patterns of positive communication, identify technical guidance, and examine the supporting and inhibiting factors faced by the principal in improving the performance of school operators in managing the Education Primary Data (DAPODIK) at SMAN 1 Muara Batu. The research employs a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. The findings indicate that strategic planning was carried out systematically and in a collaborative manner, involving school operators from the initial stages. The principal fostered positive communication through an open, empathetic, and dialogue-based approach, which helped establish a collaborative working environment. Technical guidance was provided through training, assistance, and structured supervision in the form of mentoring and coaching. Key supporting factors for the success of DAPODIK management include adequate infrastructure, flexible school policies, and inter-unit collaboration. However, several challenges were also identified, such as limited internet access, system-related technical issues, and the dual workload of school operators. Overall, the leadership strategies implemented by the principal positively impacted the competence and performance of school operators and can serve as a best practice model for digital-based education data governance in secondary education institutions